Composite silicon-carbon negative electrode plate and preparation method and application thereof

By using a three -dimensional multi -pore base and conductive polymer composite layer with porosity structures in lithium ion batteries to solve the problem of performance attenuation due to volume changes during the volume change during the cycle, the battery energy density density and Improving cycle performance.

CN119381403AInactive Publication Date: 2025-01-28JIANGSU SMART WORKSHOP TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411508545.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The silicon negative electrode in lithium-ion batteries causes particles to rupture and powder during the circulation process due to volume changes, and the SEI film continues to rupture and regenerate, resulting in rapid attenuation of battery capacity and poor circulation performance, which limits the commercial application of silicon negative electrodes.

Method used

The three -dimensional multi -pore base with pore structure is used as a collector, and the conductive polymer composite layer is set on its surface. Lithium ions are uniformly deposited to improve battery cycle performance.

Benefits of technology

Effectively alleviate the expansion of silicon particles, reduce the thickness and quality of the negative chip in the battery, improve the energy density and first charging and discharge efficiency of the battery, and improve the cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a composite silicon-carbon negative electrode plate and a preparation method and application thereof. The composite silicon-carbon negative electrode plate comprises a three-dimensional composite porous substrate and a conductive polymer composite layer arranged on at least one surface of the three-dimensional composite porous substrate. The three-dimensional composite porous substrate comprises a three-dimensional porous substrate and a silicon-carbon composite material loaded in pores of the three-dimensional porous substrate and on the surface of the three-dimensional porous substrate, the silicon-carbon composite material is of a core-shell structure, the core is a lithium supplement agent, and the shell is a silicon-carbon material with a porous structure. The conductive polymer composite layer comprises a conductive polymer and a lithium-loving metal. The volume change of silicon can be limited by utilizing the pore structure of the three-dimensional porous substrate and the conductive polymer composite layer, and meanwhile, uniform deposition of lithium ions is promoted by utilizing lithium-loving metal in the conductive polymer composite layer, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a composite silicon-carbon negative electrode sheet and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in various consumer electronic products, electric vehicles, energy storage, etc. due to their high energy density, long cycle life and environmental friendliness. Currently, the negative electrode material of lithium-ion batteries is mostly graphite, and the theoretical specific capacity of graphite is limited, which makes the improvement of lithium-ion battery energy density face a bottleneck.

[0003] Silicon anode has a very high theoretical specific capacity (4200mAh / g). If it is used in lithium battery anode, it will help improve the energy density of the battery. However, silicon-based materials will undergo huge volume changes during the process of lithium ion insertion and extraction, which will cause silicon particles to break and pulverize during battery cycling, and fall off the current collector. In addition, the huge volume change will cause the SEI film on the surface of silicon particles to continuously break and regenerate, consuming a large amount of lithium ions in the electrolyte, ultimately leading to rapid battery capacity decay and poor cycle performance, which seriously limits the commercial application of silicon anode.

[0004] In order to solve the problem of volume change during the cycle of silicon negative electrode, the conventional technical means is to coat the surface of silicon particles with a protective layer. The problem of particle pulverization caused by the volume change of silicon particles can be improved to a certain extent by coating with a protective layer, thereby improving the cycle performance of the battery, but at the same time it will reduce the overall specific capacity of the material and cause a significant decrease in the initial charge and discharge efficiency of the material, which to a certain extent reduces the role of using the high specific capacity characteristics of silicon-based negative electrode materials to prepare batteries to improve energy density.

[0005] Therefore, it is urgent to develop a new technical means to improve the expansion of silicon particles, improve the battery cycle performance, while improving the battery's initial charge and discharge efficiency and energy density. Summary of the invention

[0006] In order to solve the above technical problems, the present invention discloses a composite silicon-carbon negative electrode sheet, which can improve silicon particle expansion, improve battery cycle performance, initial charge and discharge efficiency and energy density.

[0007] To achieve the above technical objectives, the technical solution of the present invention is as follows:

[0008] The present invention provides a composite silicon-carbon negative electrode sheet, comprising a three-dimensional composite porous substrate and a conductive polymer composite layer arranged on at least one surface of the three-dimensional composite porous substrate; the three-dimensional composite porous substrate comprises a three-dimensional porous substrate and a silicon-carbon composite material loaded in the pores of the three-dimensional porous substrate and on the surface of the three-dimensional porous substrate; the conductive polymer composite layer comprises a conductive polymer and a lithium-philic metal.

[0009] The present invention proposes to use a three-dimensional porous substrate with a pore structure as a current collector, utilize the pore structure of the three-dimensional porous substrate and the conductive polymer composite layer to limit the volume change of silicon, and simultaneously utilize the lithium-philic metal in the conductive polymer composite to promote the uniform deposition of lithium ions and improve the battery cycle performance; in addition, loading the silicon-carbon composite material on the three-dimensional porous substrate with a pore structure can, on the one hand, alleviate the expansion of silicon particles, and on the other hand, reduce the thickness and mass of the negative electrode sheet in the battery, thereby improving the battery energy density.

[0010] In one embodiment of the present invention, the three-dimensional porous substrate is selected from one of carbon cloth, copper foil mesh, copper wire mesh, foam copper and foam nickel.

[0011] In one embodiment of the present invention, the pore size of the three-dimensional porous substrate is 200 nm to 800 nm.

[0012] In one embodiment of the present invention, the porosity of the three-dimensional porous substrate is 80% to 95%.

[0013] In one embodiment of the present invention, the thickness of the three-dimensional porous substrate is 30 μm to 200 μm.

[0014] In one embodiment of the present invention, the silicon-carbon composite material is a core-shell structure, wherein the core is a lithium supplement and the shell is a silicon-carbon material with a porous structure.

[0015] In one embodiment of the present invention, the silicon-carbon composite material is obtained by carbonizing a mixture of silicone oil, a lithium supplement agent, a catalyst and a silane coupling agent.

[0016] In one embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.

[0017] In one embodiment of the present invention, the conductive polymer includes at least one of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene vinylene, and polybisyne.

[0018] In one embodiment of the present invention, the lithium-philic metal includes at least one of iron, aluminum, silver, magnesium, zinc, titanium, tin, and nickel.

[0019] In one embodiment of the present invention, the thickness of the conductive polymer composite layer is 2 μm to 8 μm.

[0020] The present invention also provides a method for preparing a composite silicon-carbon negative electrode sheet, comprising the following steps:

[0021] Evenly mixing silicone oil, lithium supplement agent, catalyst and silane coupling agent to obtain a mixture;

[0022] The conductive polymer, the lithium-philic metal, the silane coupling agent and the organic solvent are uniformly mixed to obtain a mixed solution;

[0023] immersing a three-dimensional porous substrate in the mixture to obtain a three-dimensional porous substrate with the mixture attached thereto;

[0024] Carbonizing the three-dimensional porous substrate with the mixture attached thereto to obtain a three-dimensional composite porous substrate;

[0025] The mixed solution is coated on at least one surface of the three-dimensional composite porous substrate, and dried to obtain a composite silicon-carbon negative electrode sheet.

[0026] In one embodiment of the present invention, the silicone oil includes at least one of vinyl silicone oil, dimethyl silicone oil, and hydrogen-containing silicone oil.

[0027] In one embodiment of the present invention, the molecular weight of the silicone oil is 200-8000.

[0028] In one embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.

[0029] In one embodiment of the present invention, the silane coupling agent includes at least one of KH550, KH560 and KH570.

[0030] In one embodiment of the present invention, the catalyst is a platinum catalyst.

[0031] In one embodiment of the present invention, the mass ratio of the silicone oil, the lithium supplement agent, the catalyst and the silane coupling agent is (50-70): (20-30): (0.1-2): (1-2).

[0032] In one embodiment of the present invention, the conductive polymer includes at least one of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene vinylene, and polybisyne.

[0033] In one embodiment of the present invention, the lithium-philic metal includes at least one of iron, aluminum, silver, magnesium, zinc, titanium, tin, and nickel.

[0034] In one embodiment of the present invention, the silane coupling agent includes at least one of KH550, KH560 and KH570.

[0035] In one embodiment of the present invention, the organic solvent is selected from at least one of acetone, acetonitrile, ethanol, tetrahydrofuran, dimethyl ether, 1,3-dioxolane, ethylene glycol dimethyl ether, and nitrogen methyl pyrrolidone.

[0036] In one embodiment of the present invention, the mass ratio of the conductive polymer, the lithium-philic metal, the silane coupling agent and the organic solvent is (60-80):(5-15):(0.5-1.5):(60-600).

[0037] In one embodiment of the present invention, the carbonization treatment includes a first heat treatment and a second heat treatment.

[0038] In one embodiment of the present invention, the temperature of the first heat treatment is 80-145° C., and the time of the first heat treatment is 30-50 minutes.

[0039] In one embodiment of the present invention, the temperature of the second heat treatment is 700-950° C., and the time of the second heat treatment is 6-15 hours.

[0040] In one embodiment of the present invention, the drying temperature is 80-150° C., and the drying time is 20-120 min.

[0041] The present invention provides a secondary battery, comprising the composite silicon-carbon negative electrode sheet or the composite silicon-carbon negative electrode sheet prepared by the above preparation method.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] 1. The present invention uses a three-dimensional porous substrate with a pore structure as a current collector, uses the pore structure of the three-dimensional porous substrate and the conductive polymer composite layer to limit the volume change of silicon, and uses the lithium-philic metal in the conductive polymer composite to promote the uniform deposition of lithium ions, which can improve the battery cycle performance. In addition, loading the silicon-carbon composite material on a three-dimensional porous substrate with a pore structure can alleviate the expansion of silicon particles, reduce the thickness and mass of the negative electrode sheet in the battery, and improve the battery energy density and the initial charge and discharge efficiency.

[0044] 2. The present invention uses silicone oil, lithium replenisher, catalyst and silane coupling agent as precursors of silicon-carbon composite materials to prepare a composite material with a lithium replenisher as the core and a silicon-carbon material as the outer coating layer. Since the silicone oil forms a silicon-carbon material with a specific porous structure after a series of catalytic polymerization and carbonization reactions, it can provide a certain buffer expansion space. At the same time, the lithium replenisher can play a lithium replenishing effect during the battery cycle to improve the battery cycle performance. After decomposition, it can provide a larger buffer expansion space to alleviate the battery expansion problem.

[0045] 3. The preparation method provided in this application is simple to operate, has low energy consumption, and is convenient for industrial production. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0047] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0048] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0049] The conventional technical means to improve the volume change problem of silicon negative electrode in the existing silicon negative electrode cycle is to coat the surface of silicon particles with a protective layer. Although the coating with a protective layer can improve the problem of particle pulverization caused by the volume change of silicon particles to a certain extent, it will reduce the overall specific capacity of the material and cause the first charge and discharge efficiency of the material to be significantly reduced, which to a certain extent reduces the role of using the high specific capacity characteristics of silicon-based negative electrode materials to prepare batteries to improve energy density. The present invention proposes to use a three-dimensional porous substrate with a pore structure as a current collector, and use the pore structure of the three-dimensional porous substrate and the conductive polymer composite layer to limit the volume change of silicon. At the same time, the lithium-philic metal in the conductive polymer composite is used to promote the uniform deposition of lithium ions and improve the battery cycle performance; in addition, the three-dimensional porous substrate with a pore structure is loaded with a silicon-carbon composite material, which can alleviate the expansion of silicon particles, reduce the thickness and mass of the negative electrode sheet in the battery, and improve the battery energy density and the first charge and discharge efficiency. While improving the problem of silicon particle volume change, it is achieved that the high specific capacity characteristics of silicon-based negative electrode materials are guaranteed to prepare batteries to improve energy density.

[0050] To achieve the above technical objectives, the technical solution of the present invention is as follows:

[0051] The present invention provides a composite silicon-carbon negative electrode sheet, comprising a three-dimensional composite porous substrate and a conductive polymer composite layer arranged on at least one surface of the three-dimensional composite porous substrate; the three-dimensional composite porous substrate comprises a three-dimensional porous substrate and a silicon-carbon composite material loaded in the pores of the three-dimensional porous substrate and on the surface of the three-dimensional porous substrate; the conductive polymer composite layer comprises a conductive polymer and a lithium-philic metal.

[0052] In one embodiment of the present invention, the three-dimensional porous substrate is selected from one of carbon cloth, copper foil mesh, copper wire mesh, foam copper and foam nickel.

[0053] In one embodiment of the present invention, the pore size of the three-dimensional porous substrate is 200nm to 800nm.

[0054] In one embodiment of the present invention, the porosity of the three-dimensional porous substrate is 80% to 95%.

[0055] In one embodiment of the present invention, the thickness of the three-dimensional porous substrate is 30 μm to 200 μm.

[0056] In one embodiment of the present invention, the silicon-carbon composite material is a core-shell structure, wherein the core is a lithium supplement and the shell is a silicon-carbon material with a porous structure.

[0057] In one embodiment of the present invention, the silicon-carbon composite material is obtained by carbonizing a mixture of silicone oil, a lithium supplement agent, a catalyst and a silane coupling agent.

[0058] In one embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.

[0059] In one embodiment of the present invention, the conductive polymer includes at least one of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene vinylene, and polybisyne.

[0060] In one embodiment of the present invention, the lithium-philic metal includes at least one of iron, aluminum, silver, magnesium, zinc, titanium, tin, and nickel.

[0061] In one embodiment of the present invention, the thickness of the conductive polymer composite layer is 2 μm to 8 μm.

[0062] In one embodiment of the present invention, the conductive polymer composite layer also includes a silane coupling agent, which not only improves the bonding strength between the conductive polymer and the lithium-philic metal, but also links the conductive polymer and the silicon-carbon composite material in the three-dimensional porous composite substrate, thereby improving battery performance.

[0063] The present invention also provides a method for preparing a composite silicon-carbon negative electrode sheet, comprising the following steps:

[0064] Evenly mixing silicone oil, lithium supplement agent, catalyst and silane coupling agent to obtain a mixture;

[0065] The conductive polymer, the lithium-philic metal, the silane coupling agent and the organic solvent are uniformly mixed to obtain a mixed solution;

[0066] immersing a three-dimensional porous substrate in the mixture to obtain a three-dimensional porous substrate with the mixture attached thereto;

[0067] Carbonizing the three-dimensional porous substrate with the mixture attached thereto to obtain a three-dimensional composite porous substrate;

[0068] The mixed solution is coated on at least one surface of the three-dimensional composite porous substrate, and dried to obtain a composite silicon-carbon negative electrode sheet.

[0069] In one embodiment of the present invention, the silicone oil includes at least one of vinyl silicone oil, dimethyl silicone oil, and hydrogen-containing silicone oil.

[0070] In one embodiment of the present invention, the molecular weight of the silicone oil is 200-8000. Specifically, the molecular weight of the silicone oil can be any one of 200, 300, 500, 650, 800, 950, 1200, 1450, 1600, 1850, 2000, 2200, 2400, 2600, 2800, 3200, 3500, 3800, 4200, 4500, 4800, 5100, 5500, 6000, 6500, 7000, 7500 or 8000. Preferably, the molecular weight of the silicone oil is 200-5000. The molecular weight of the silicone oil should not be too large, as a large amount of the silicone oil will result in excessive viscosity of the mixture, which is not conducive to the immersion of the mixture into the pores of the three-dimensional porous substrate, thereby reducing the restriction effect of the pore structure of the three-dimensional porous substrate on the silicon-carbon composite material and poorly inhibiting expansion.

[0071] In one embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.

[0072] In one embodiment of the present invention, the silane coupling agent includes at least one of KH550, KH560 and KH570.

[0073] In one embodiment of the present invention, the catalyst is a platinum catalyst.

[0074] In one embodiment of the present invention, the mass ratio of the silicone oil, the lithium supplement agent, the catalyst and the silane coupling agent is (50-70): (20-30): (0.1-2): (1-2).

[0075] In one embodiment of the present invention, the three-dimensional porous substrate is selected from one of carbon cloth, copper foil mesh, copper wire mesh, foam copper, and foam nickel. Preferably, the three-dimensional porous substrate is carbon cloth, which can achieve better contact between the three-dimensional porous substrate and the silicon-carbon composite material during the carbonization process, thereby avoiding the silicon-carbon composite material from expanding and pulverizing during subsequent cycles, causing the silicon-carbon composite material to fall off from the pores of the three-dimensional porous substrate.

[0076] The pore size of the three-dimensional porous substrate pores should not be too large or too small. If it is too small, it will be unfavorable for the embedding of the mixture; if it is too large, the particle size of the silicon-carbon composite material in the three-dimensional porous substrate will be too large, and the restrictive effect of the skeleton of the three-dimensional porous substrate on the silicon-carbon composite material will be weakened. Preferably, the pore size of the three-dimensional porous substrate pores is 200nm to 800nm. Specifically, the pore size of the three-dimensional porous substrate pores can be 200nm to 400nm, 300nm to 500nm, 400nm to 600nm, 500nm to 700nm, 600nm to 800nm ​​or any range value within 200nm to 800nm. The pores of the three-dimensional porous substrate are limited to the nanometer level, which can better alleviate the expansion of the silicon-carbon composite material.

[0077] The porosity of the pores of the three-dimensional porous substrate should not be too large or too small. If it is too small, the embedding amount of the mixture is small and a good energy density cannot be achieved; if it is too large, the restriction effect of the skeleton of the three-dimensional porous substrate on the silicon-carbon composite material will be weakened. Preferably, the porosity of the three-dimensional porous substrate is 80% to 95%. Specifically, the porosity of the three-dimensional porous substrate can be 80%, 85%, 90%, 95% or any value in the range of 80% to 95%.

[0078] In one embodiment of the present invention, the thickness of the three-dimensional porous substrate is 30 μm to 200 μm. The thickness of the three-dimensional porous substrate can be reasonably selected in combination with the battery capacity and energy density setting requirements, as well as the loading amount of the silicon-carbon composite material.

[0079] In one embodiment of the present invention, the conductive polymer includes at least one of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene vinylene, and polybisyne.

[0080] In one embodiment of the present invention, the lithium-philic metal includes at least one of iron, aluminum, silver, magnesium, zinc, titanium, tin, and nickel.

[0081] In one embodiment of the present invention, the silane coupling agent includes at least one of KH550, KH560 and KH570.

[0082] In one embodiment of the present invention, the organic solvent is selected from at least one of acetone, acetonitrile, ethanol, tetrahydrofuran, dimethyl ether, 1,3-dioxolane, ethylene glycol dimethyl ether, and nitrogen methyl pyrrolidone.

[0083] In one embodiment of the present invention, the mass ratio of the conductive polymer, the lithium-philic metal, the silane coupling agent and the organic solvent is (60-80):(5-15):(0.5-1.5):(60-600).

[0084] In one embodiment of the present invention, the carbonization treatment includes a first heat treatment and a second heat treatment.

[0085] In one embodiment of the present invention, the temperature of the first heat treatment is 80-145°C, and the time of the first heat treatment is 30-50 minutes. During the first heat treatment, under the action of temperature and catalyst, the silicone oil undergoes self-polymerization reaction, thereby preparing a silicon-carbon composite material precursor, wherein the silicon-carbon composite material precursor is a core-shell structure, wherein the core is a lithium supplement and the outer shell is silicone oil that undergoes polymerization reaction.

[0086] In one embodiment of the present invention, the temperature of the second heat treatment is 700-950°C, and the time of the second heat treatment is 6-15 hours. Through the high temperature of the second heat treatment, the silicone oil shell that undergoes polymerization reaction is carbonized to form a silicon-carbon material with a porous structure, thereby forming a silicon-carbon composite material.

[0087] In one embodiment of the present invention, the method of coating the mixed solution on at least one surface of the three-dimensional composite porous substrate can be scraping, spraying or any other coating method commonly used in the art.

[0088] In one embodiment of the present invention, the drying temperature is 80-150° C., and the drying time is 20-120 min. The drying equipment can be oven drying or other commonly used drying equipment in the art.

[0089] The present invention provides a secondary battery, comprising the composite silicon-carbon negative electrode sheet or the composite silicon-carbon negative electrode sheet prepared by the above preparation method.

[0090] In one embodiment of the present invention, the secondary battery further comprises a positive electrode sheet, a separator and an electrolyte. In the present application, the composition ratio and preparation method of the positive electrode sheet, the separator and the electrolyte are not limited and conventional operations in the art may be used.

[0091] Specifically, the positive electrode active material in the positive electrode sheet may include at least one of lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium iron phosphate, lithium iron manganese fluorophosphate, and lithium nickel iron manganese oxide; the material of the diaphragm may include at least one of polyethylene, polypropylene, polyacrylonitrile, polyvinyl alcohol, polyarylether sulfone, and polyvinylidene fluoride; the solvent in the electrolyte may include a carbonate solvent and / or an ether solvent, and the lithium salt in the electrolyte may include at least one of LiPF6, LiBF4, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2.

[0092] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0093] Example 1

[0094] This embodiment provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0095] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:30:0.5:2 to obtain a mixture;

[0096] The conductive polymer polypyrrole, the lithium-philic metal silver, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:10:1:200 to obtain a mixed solution;

[0097] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500 nm to 800 nm, porosity of 88%, thickness of 120 μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0098] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0099] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0100] Example 2

[0101] This embodiment provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0102] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are mixed uniformly in a mass ratio of 70:30:0.8:2 to obtain a mixture;

[0103] The conductive polymer polypyrrole, the lithium-philic metal silver, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:10:1:200 to obtain a mixed solution;

[0104] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500nm to 800nm, porosity of 88%, thickness of 120μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0105] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0106] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0107] Example 3

[0108] This embodiment provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0109] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are mixed uniformly in a mass ratio of 50:30:0.3:2 to obtain a mixture;

[0110] The conductive polymer polypyrrole, the lithium-philic metal silver, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:10:1:200 to obtain a mixed solution;

[0111] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500nm to 800nm, porosity of 88%, thickness of 120μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0112] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0113] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0114] Example 4

[0115] This embodiment provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0116] Dimethyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:30:0.5:2 to obtain a mixture;

[0117] The conductive polymer polypyrrole, the lithium-philic metal silver, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:10:1:200 to obtain a mixed solution;

[0118] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500 nm to 800 nm, porosity of 88%, thickness of 120 μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0119] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0120] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0121] Example 5

[0122] This embodiment provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0123] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:30:0.5:2 to obtain a mixture;

[0124] The conductive polymer polypyrrole, the lithium-philic metal silver, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:8:1.5:200 to obtain a mixed solution;

[0125] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500 nm to 800 nm, porosity of 88%, thickness of 120 μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0126] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0127] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0128] Example 6

[0129] This embodiment provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0130] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:30:0.5:2 to obtain a mixture;

[0131] The conductive polymer polythiophene, the lithium-philic metal titanium, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:10:1:200 to obtain a mixed solution;

[0132] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500 nm to 800 nm, porosity of 88%, thickness of 120 μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0133] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0134] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0135] Example 7

[0136] This embodiment provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0137] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:30:0.5:2 to obtain a mixture;

[0138] The conductive polymer polypyrrole, the lithium-philic metal silver, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:10:1:200 to obtain a mixed solution;

[0139] Immersing a three-dimensional porous substrate copper foam (pore size of 500nm to 800nm, porosity of 88%, thickness of 120μm) into the mixture to obtain a three-dimensional porous substrate with the mixture attached thereto;

[0140] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0141] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0142] Comparative Example 1

[0143] This comparative example provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0144] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:30:0.5:2 to obtain a mixture;

[0145] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500nm to 800nm, porosity of 88%, thickness of 120μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0146] The three-dimensional porous substrate with the mixture attached was carbonized, first heated at 120°C for 45 minutes, and then carbonized at 850°C for 12 hours to obtain a three-dimensional composite porous substrate as a composite silicon-carbon negative electrode sheet.

[0147] Comparative Example 2

[0148] This comparative example provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0149] Vinyl silicone oil, lithium supplement agent lithium powder, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:30:0.5:2 to obtain a mixture;

[0150] The conductive polymer polypyrrole, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:1:200 to obtain a mixed solution;

[0151] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500nm to 800nm, porosity of 88%, thickness of 120μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0152] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0153] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0154] Comparative Example 3

[0155] This comparative example provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0156] Vinyl silicone oil, platinum catalyst and silane coupling agent KH550 are uniformly mixed in a mass ratio of 60:0.5:2 to obtain a mixture;

[0157] The conductive polymer polypyrrole, the lithium-philic metal silver, the silane coupling agent KH550 and the organic solvent acetone are uniformly mixed in a mass ratio of 70:10:1:200 to obtain a mixed solution;

[0158] Immersing a three-dimensional porous matrix carbon cloth (pore size of 500nm to 800nm, porosity of 88%, thickness of 120μm) in the mixture to obtain a three-dimensional porous matrix with the mixture attached thereto;

[0159] The three-dimensional porous substrate with the mixture attached thereto is subjected to a carbonization treatment, firstly heated at a temperature of 120° C. for 45 minutes, and then carbonized at a temperature of 850° C. for 12 hours, to obtain a three-dimensional composite porous substrate;

[0160] The mixed solution was evenly coated on both sides of the three-dimensional composite porous substrate by a blade coating method, and dried at a drying temperature of 100° C. for 45 minutes to obtain a composite silicon-carbon negative electrode sheet with a single-sided conductive polymer composite layer having a thickness of 5 μm.

[0161] Comparative Example 4

[0162] This comparative example provides a method for preparing a composite silicon-carbon negative electrode sheet:

[0163] Silicon-carbon composite negative electrode material is used to prepare silicon-carbon composite negative electrode sheet through conventional lithium battery negative electrode batching and coating process. Specifically, silicon-carbon negative electrode material is mixed with modified artificial graphite (silicon-carbon negative electrode material accounts for 15% by mass), carbon nanotube conductive material, and bonding material (95wt% sodium carboxymethyl cellulose and 5wt% styrene-butadiene rubber), and the mass percentages are 96%, 1.5%, and 2.5%, and deionized water is added for stirring, the solid content is controlled at 50%, and the viscosity is adjusted to 3100mPa.s to obtain negative electrode slurry, which is coated on copper foil, dried, and pressed to obtain a silicon negative electrode sheet with a thickness of 120μm.

[0164] Preparation of lithium-ion batteries:

[0165] The composite silicon-carbon negative electrode sheet, separator, and nickel-cobalt-manganese-oxide positive electrode sheet prepared in the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 4 are wound to obtain a battery cell, and the battery cell is placed in a battery shell, dried, electrolyte injected, packaged, formed, and volume divided to obtain a lithium-ion battery. Among them, the positive electrode sheet is: lithium nickel-cobalt-manganese-oxide is mixed with a conductive agent (conductive carbon black and carbon nanotubes are mixed in a mass ratio of 19:1) and a PVDF adhesive material in a mass ratio of 97.5:1.5:1, mixed with NMP as a solvent and then coated on an aluminum foil, and dried, rolled, cut, and striped to obtain a positive electrode sheet; the separator is a polyethylene separator; the electrolyte is prepared by dissolving LiPF6 in a solvent EC&DMC (volume ratio 1:1), and the LiPF6 concentration is 1M.

[0166] Electrical performance test: The lithium ion batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were subjected to energy density tests, and the first coulombic efficiency and cycle performance (number of cycles corresponding to a capacity decay to 80%) were tested at 25°C, 1C / 1C, and a charge and discharge voltage range of 2.75V to 4.25V. The test results are shown in Table 1.

[0167] The electrical performance test results of the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 4 are shown in Table 1.

[0168] Table 1 Electrical performance test results of Examples 1 to 7 and Comparative Examples 1 to 4

[0169] First coulombic efficiency (%) Number of cycles (circles) Energy density (Wh / kg) Example 1 90.5% 1168 416 Example 2 90.9% 1215 426 Example 3 91.3% 1247 405 Example 4 90.6% 1189 421 Example 5 90.5% 1096 413 Example 6 90.3% 1079 418 Example 7 90.1% 1068 420 Comparative Example 1 88.8% 827 412 Comparative Example 2 89.1% 994 403 Comparative Example 3 89.7% 975 398 Comparative Example 4 85.3% 549 316

[0170] From the results in Table 1, it can be seen that the lithium ion battery prepared by the composite silicon-carbon negative electrode sheet prepared by the method of the present invention has an improved energy density, and the first coulombic efficiency and cycle performance are greatly improved compared with the lithium ion battery prepared by the conventional silicon-carbon composite negative electrode sheet (Comparative Example 1).

[0171] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite silicon-carbon negative electrode sheet, characterized in that: It includes a three-dimensional composite porous substrate and a conductive polymer composite layer arranged on at least one surface of the three-dimensional composite porous substrate; the three-dimensional composite porous substrate includes a three-dimensional porous substrate and a silicon-carbon composite material loaded in the pores of the three-dimensional porous substrate and on the surface of the three-dimensional porous substrate; the conductive polymer composite layer includes a conductive polymer and a lithium-philic metal.

2. The composite silicon-carbon negative electrode sheet according to claim 1, characterized in that: The three-dimensional porous substrate is selected from one of carbon cloth, copper foil mesh, copper wire mesh, foam copper, and foam nickel; The silicon-carbon composite material is a core-shell structure, wherein the core is a lithium supplement and the shell is a silicon-carbon material with a porous structure.

3. The composite silicon-carbon negative electrode sheet according to claim 2, characterized in that: The lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.

4. The composite silicon-carbon negative electrode sheet according to claim 1, characterized in that: The conductive polymer comprises at least one of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene ethylene, and polybisyne; And / or, the lithium-philic metal includes at least one of iron, aluminum, silver, magnesium, zinc, titanium, tin, and nickel.

5. The composite silicon-carbon negative electrode sheet according to claim 1, characterized in that: The thickness of the conductive polymer composite layer is 2 μm to 8 μm.

6. A method for preparing a composite silicon-carbon negative electrode sheet, characterized in that: The following steps are involved: Evenly mixing silicone oil, lithium supplement agent, catalyst and silane coupling agent to obtain a mixture; The conductive polymer, the lithium-philic metal, the silane coupling agent and the organic solvent are uniformly mixed to obtain a mixed solution; immersing a three-dimensional porous substrate in the mixture to obtain a three-dimensional porous substrate with the mixture attached thereto; Carbonizing the three-dimensional porous substrate to which the mixture is attached to obtain a three-dimensional composite porous substrate; The mixed solution is coated on at least one surface of the three-dimensional composite porous substrate, and dried to obtain a composite silicon-carbon negative electrode sheet.

7. The preparation method according to claim 6, characterized in that: The silicone oil includes at least one of vinyl silicone oil, dimethyl silicone oil and hydrogen-containing silicone oil; The lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2; The catalyst is a platinum catalyst; The mass ratio of the silicone oil, the lithium supplement agent, the catalyst and the silane coupling agent is (50-70): (20-30): (0.1-2): (1-2).

8. The preparation method according to claim 6, characterized in that: The conductive polymer comprises at least one of polyacetylene, polythiophene, polypyrrole, polyaniline, polyphenylene, polyphenylene ethylene, and polybisyne; The lithium-philic metal includes at least one of iron, aluminum, silver, magnesium, zinc, titanium, tin, and nickel; The organic solvent is selected from at least one of acetone, acetonitrile, ethanol, tetrahydrofuran, dimethyl ether, 1,3-dioxolane, ethylene glycol dimethyl ether, and nitrogen methyl pyrrolidone; The mass ratio of the conductive polymer, the lithium-philic metal, the silane coupling agent and the organic solvent is (60-80):(5-15):(0.5-1.5):(60-600).

9. The preparation method according to claim 6, characterized in that: The carbonization treatment includes a first heat treatment and a second heat treatment; The temperature of the first heat treatment is 80 to 145° C., and the time of the first heat treatment is 30 to 50 minutes; The temperature of the second heat treatment is 700-950° C., and the time of the second heat treatment is 6-15 hours.

10. A secondary battery, characterized in that: It comprises the composite silicon-carbon negative electrode sheet as described in any one of claims 1 to 5 or the composite silicon-carbon negative electrode sheet prepared by the preparation method as described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Composite negative material adopting three-dimensional porous carbon to coat silicon and preparation method thereof

    CN107346820A

  • 3D alloy lithium cathode, preparation method thereof and lithium secondary battery

    CN109728242A

  • Silicon-carbon composite negative electrode material, preparation method thereof and lithium ion battery

    CN113725422A

  • Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and secondary battery

    CN114044516A

  • Composite current collector and preparation method and application thereof

    CN118431485A